Survival after severe amitriptyline poisoning with prolonged ventricular tachycardia and cardiac arrest - Abeyaratne, D.D.K.; Liyanapathirana, C.; Gamage, A.; Karunarathne, P.; Botheju, M.; Indrakumar, J. (BMC Research Notes, 2016)
Attached

Background: Tricyclic antidepressants (TCA) are becoming one of the most frequently used substances in self poi- - soning. Significant morbidity and mortality associated with TCA overdose are often related to and refractory hypotension. We report the first case of survival after severe amitriptyline poisoning, leading to prolonged cardiac arrest and ’ ventricular tachycardia (VT), resuscitated with 3 h of uninterrupted cardiac massage and Direct current (DC) shocks. Case presentation: A 25 year old girl presented with severe amitriptyline poisoning causing pulseless VT and prolonged cardiac arrest. After 3 h of uninterrupted external cardiac massage, together with nine DC shocks and intra venous bicarbonate injections the rhythm reverted to a nodal tachycardia, initial 2D echocardiogram showed left ventricular dysfunction, which recovered to normal after 2 weeks and the patient had a complete recovery subsequently. Conclusion: Our case highlights the importance of continued resuscitation in patients presenting with TCA poisoning and resistant arrhythmia, especially in young and otherwise healthy patients
Keywords: Tricyclic antidepressants; Cardiac arrhythmia; Prolonged cardiac arrest